Botanical Drugs and Stem Cells - Po-Cheng Lin; Li-Fu Chang; Po-Yen Liu; Shinn-Zong Lin; Wan-Chen Wu; Wuen-Shyong Chen; Chang-Hai Tsai; Tzyy-Wen Chiou Ph.D.; Horng-Jyh Harn (Cell Transplantation, 2011)
The potential to generate virtually any differentiated cell type from stem cells offers the possibility of creating new sources of cells for regenerative medicine. To realize this potential, it will be essential to control stem cell differentiation. Chinese herbal medicine is a major aspect of traditional Chinese medicine and is a rich source of unique chemicals. As such, individual herbs or extracts may play a role in the proliferation and differentiation of stem cells. In this review, we discuss some of the Chinese herbal medicines that are used to treat human diseases such as neuronal degenerative diseases, cardiovascular diseases, and osteoporosis. We also describe the relationship between Chinese herbal medicines and stem cell regulation.